2021
DOI: 10.3390/ijerph18147436
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bacterial Microbiomes in Association with Potential Prediabetes Using Different Criteria of Diagnosis

Abstract: This study aimed to find a potential biomarker that can be used to diagnose prediabetic condition by comparing the salivary bacterial microbiomes between Thai dental patients with normoglycemia (NG) and those with potential prediabetes (PPG) conditions. Thirty-three subjects were randomly recruited. Demographic data were collected along with oral examination and unstimulated salivary collections. The salivary bacterial microbiomes were identified by high-throughput sequencing on the V3–V4 region of the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Stomatobaculum has also not previously been linked to autism but has been identified as a metagenomic biomarker for oral cancer ( Eun et al, 2021 ). Furthermore, this bacterial genus has been related to prediabetic conditions ( Rungrueang et al, 2021 ) and reflux ( Liang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stomatobaculum has also not previously been linked to autism but has been identified as a metagenomic biomarker for oral cancer ( Eun et al, 2021 ). Furthermore, this bacterial genus has been related to prediabetic conditions ( Rungrueang et al, 2021 ) and reflux ( Liang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human saliva contains abundant biological information, and the oral flora can reflect various physiological and pathological changes of the human body. Amr and Kornwipa [ 42 , 43 ] found that the number of species in oral saliva decreased with the progression of diabetes, and that diabetics exhibited the largest pathogenic microbiome. However, the sample size of their researches was small, the changes of oral microflora in prediabetic patients need to be further explored in a larger sample.…”
Section: Discussionmentioning
confidence: 99%
“…An important observation from the opposite view of the periodontitis-diabetes relationship, is that periodontal treatment impacts glycaemic control and inflammatory markers in T2DM (20). And interestingly, a 2021 article identified specific microbial clusters in periodontitis which could be potentially used as a marker for pre-diabetes (21).…”
Section: Chronic Periodontal Diseasementioning
confidence: 99%